1991
DOI: 10.1093/nar/19.3.477
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotides within both proximal and distal parts of the consensus sequence are important for specific DNA recognition by the herpes simplex virus regulatory protein ICP4

Abstract: The herpes simplex virus type 1 regulatory protein ICP4 is a sequence specific DNA binding protein which associates with a number of different sites, some of which include the consensus ATCGTCnnnnYCGRC. In order to investigate the involvement in DNA binding of conserved bases within the consensus, we have synthesised a family of mutant oligonucleotides and tested their ability to form a complex with ICP4. We have also compared the binding specificities of bacterially expressed fragments of ICP4 which include t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 29 publications
(30 reference statements)
2
29
0
Order By: Relevance
“…Cloning and expression of the DNA binding domain of 140k in a T7 expression vector and its subsequent partial purification Gene 62, encoding the 140k protein, lies in the left repeat bounding the short unique segment of the VZV genome ( ;46 417I 546 417 expressed in isolation and found to have a similar binding specificity to that of the intact protein (21,25,31). Our intention was to express the equivalent region of the homologous VZV JE protein 140k, encompassing its DNA binding domain, in order to study its DNA binding characteristics for comparison with those of the HSV-1 Vmw175 DNA binding domain.…”
Section: Resultsmentioning
confidence: 99%
“…Cloning and expression of the DNA binding domain of 140k in a T7 expression vector and its subsequent partial purification Gene 62, encoding the 140k protein, lies in the left repeat bounding the short unique segment of the VZV genome ( ;46 417I 546 417 expressed in isolation and found to have a similar binding specificity to that of the intact protein (21,25,31). Our intention was to express the equivalent region of the homologous VZV JE protein 140k, encompassing its DNA binding domain, in order to study its DNA binding characteristics for comparison with those of the HSV-1 Vmw175 DNA binding domain.…”
Section: Resultsmentioning
confidence: 99%
“…l a). A consensus IE175K recognition site of the form ATCGTCnnnnyC/G G (n is any base) has been proposed in several studies (Faber & Wilcox, 1988;DiDonato et al, 1991;Pizer et al, 1991). Two potential IE175K binding sites in LAP, which are similar to the consensus and form an imperfect inverted palindrome, are indicated by dashed arrows (Fig.…”
Section: Binding Of Le175k To Lap Cap Site Sequencesmentioning
confidence: 99%
“…The results of DeLuca & Schaffer (1988) indicated that large regions of IE175K could be deleted without affecting DNA binding. Moreover, small recombinant IE175K variants expressed in E. coli were sufficient for DNA binding and for dimerization (Wu & Wilcox, 1990;Everett et al, 1991;Pizer et at., 1991). Bacterial fusion proteins FP449 and FP525, containing IE175K residues 262 to 490 that span the DNA-binding domain (Wu & Wilcox, 1990), were therefore tested to determine whether they retained the capacity to form complex C2.…”
Section: Protein Requirements For C2 Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmids pT7I9, pT7I9X, pT7I10 and pT7I10X, which express variations of the DNA binding domain of Vmw175 from the p585.4 vector (based on pET8c), have been described previously Pizer et al, 1991). Plasmids were constructed and maintained in E. coli strain DH5 and expression was induced in strain BL21(DE3)pLysS (Studier et al, 1990).…”
Section: Methodsmentioning
confidence: 99%